Piezoelectric Electromechanical Transducers for Underwater Sound, Part I. - S. Aronov, Boris (Boston, MA : Academic Studies Press, 2022)
A comprehensive yet practical treatment of piezoelectric transducers for underwater sound.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books